2019
DOI: 10.1186/s12903-019-0720-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronodentistry: the role & potential of molecular clocks in oral medicine

Abstract: Molecular clocks help organisms to adapt important physiological functions to periodically changing conditions in the environment. These include the adaption of the 24 h sleep-wake rhythm to changes of day and night. The circadian clock is known to act as a key regulator in processes of health and disease in different organs. The knowledge on the circadian clock led to the development of chronopharmacology and chronotherapy. These fields aim to investigate how efficiency of medication and therapies can be impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 96 publications
(99 reference statements)
0
21
0
1
Order By: Relevance
“…A chronotherapeutic approach to the use of CFA improves the clinical efficacy of NSPT. [ 44 45 ] It has been proven that pharmacokinetics and pharmacodynamics follow the circadian rhythms: optimizing the timing of medication administration taking into account that circadian fluctuations can increase the effectiveness of therapeutic measures. [ 45 46 ] Chronotherapy also reduces side effects and improves the overall drug safety.…”
Section: Discussionmentioning
confidence: 99%
“…A chronotherapeutic approach to the use of CFA improves the clinical efficacy of NSPT. [ 44 45 ] It has been proven that pharmacokinetics and pharmacodynamics follow the circadian rhythms: optimizing the timing of medication administration taking into account that circadian fluctuations can increase the effectiveness of therapeutic measures. [ 45 46 ] Chronotherapy also reduces side effects and improves the overall drug safety.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, PER and CRY proteins multimerize with another core circadian regulator, casein kinase I δ in the cytoplasm and enter the nucleus to inhibit the activity of BMAL1/CLOCK complexes ( St. John et al, 2014 ). Both genes are involved in the circadian regulation of several physiological (e.g., bone metabolism) and pathological processes (e.g., development of cancer) ( Adeola et al, 2019 ; Janjiæ and Agis, 2019 ). In enamel, we have previously demonstrated that both Bmal1 and Per2 are robustly expressed by pre-ameloblast and differentiating ameloblasts in both human and mice embryonic teeth in addition to mice postnatal teeth ( Zheng et al, 2011 , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of hCRY2, hPER3 and hBMAL1 in tumoral tissues vs. their non-cancerous adjacent counterparts has been previously correlated with severity of tumor progression in a retrospective cohort of 40 head and neck squamous cell carcinoma patients (Hsu et al, 2012). A recent review article has further detailed the importance of circadian clock biology and its potential in various fields of dentistry (Janjic and Agis, 2019).…”
Section: Circadian Clock Oral Tissues Homeostasis and Head And Neckmentioning
confidence: 99%